2005
DOI: 10.1158/1078-0432.ccr-04-0465
|View full text |Cite
|
Sign up to set email alerts
|

Isochromosome 17q Is a Negative Prognostic Factor in Poor-Risk Childhood Medulloblastoma Patients

Abstract: Medulloblastomas are genetically heterogeneous and can be categorized into separate genetic subgroups by their CNAs using unsupervised cluster analysis and SAM. i(17)(q10) was a significant independent negative prognostic factor. Infant medulloblastomas may be a distinct genetic subset from those of older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 31 publications
1
10
0
2
Order By: Relevance
“…Isochromosome 17q (i17q) is one of the most frequent recurring abnormalities in medulloblastoma, occurring in approximately 40-50% of cases, predominantly within the Group 4/D subtype in adults. 7 It has been reported to be a negative prognostic factor; 8,9 in childhood medulloblastoma, it has been commonly associated with mutations in TP53 and desmoplastic histology 10 , which was consistent with what we found in our case despite its occurrence in an adult. A predominant difference is that studies in the childhood form associated 17p loss with the SHH subgroup.…”
Section: Clinical Case Reportsupporting
confidence: 92%
“…Isochromosome 17q (i17q) is one of the most frequent recurring abnormalities in medulloblastoma, occurring in approximately 40-50% of cases, predominantly within the Group 4/D subtype in adults. 7 It has been reported to be a negative prognostic factor; 8,9 in childhood medulloblastoma, it has been commonly associated with mutations in TP53 and desmoplastic histology 10 , which was consistent with what we found in our case despite its occurrence in an adult. A predominant difference is that studies in the childhood form associated 17p loss with the SHH subgroup.…”
Section: Clinical Case Reportsupporting
confidence: 92%
“…Eberhart et al have shown that moderate to severe anaplasia in medulloblastoma cells is also associated with poor survival [6]. Additionally, large-scale genomic changes such as isochromosome 17q, with loss of chromosome 17p and gain of 17q, present in 30–50 % of medulloblastomas, are associated with poor prognosis [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Presence of isochromosome 17q serves as a negative prognosis indicator [12]. The mechanism by which this abnormality plays a role in tumorigenesis has not been clearly elucidated.…”
Section: Biologymentioning
confidence: 99%
“…Chromosome arm17p contains several tumor supressor genes, and thus it is postulated that deletion of this gene region may be the culprit. One of these genes is the tumor suppressor p53 [9, 1214]. …”
Section: Biologymentioning
confidence: 99%